Posture correction system of squat using EMG and 6-axis acceleration sensor - Min, Hwangsung; Won, Songchang; Yeom, Hojun (International Journal of Engineering and Technology, 2018)
Recently, the need for fitness for health and appearance has increased and interest in fitness has been increasing. Because of the cost of personal training (PT), many people are doing exercise at home. However, when the correct feedback is not received, the exercise is performed in a wrong posture, resulting in frequent cases of injuries or sprains.In this study, we developed an exercise posture correcting device to exercise alone at home. Especially, we have studied squat which many people are doing individually. The EMG module is placed on both thighs to receive the signal, and the EMG of the main muscle is compared with the EMG of the correct posture. At the same time, the MPU-6050, which is a 6-axis acceleration sensor, measures the angle of the knee and the degree of sitting. We will develop a system that enables feedback.Â Â